Preparation method and application of CoFe2O4-coated BaTiO3 nano core-shell particles
CoFe2O4@BaTiO3 nano core-shell particles were prepared by hydrothermal method, which solved the problems of poor decomposition performance of organic pollutants in wastewater and low catalyst recovery efficiency in the prior art, and achieved efficient photocatalysis and catalyst recycling.
Patent Information
- Application Number
- CN202510055102.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when dealing with sewage wastewater generated in pharmaceutical, chemical and other industries, it is difficult to effectively decompose organic pollutants, and the catalyst recycling and recycling efficiency is low, which easily leads to secondary pollution.
CoFe2O4@BaTiO3 nano core-shell particles were prepared by hydrothermal method, and CoFe2O4 was used as the core and BaTiO3 as the shell to form a magnetically recoverable photocatalyst.
The photocatalytic performance and the efficiency of the catalyst recycling are improved, secondary pollution is reduced, and the particle size of the catalyst is uniformly distributed and there are no impurities.
Smart Images

Figure CN119869531A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation, and specifically relates to a preparation method and application of CoFe2O4@BaTiO3 nano core-shell particles. Background Art
[0002] The sewage and wastewater produced by the pharmaceutical, chemical and other industries contain a large amount of toxic and harmful organic compounds, which not only destroy the ecological balance, but also greatly affect human health and cause species to be infected with diseases. At present, in order to solve the pollution problem of water bodies, physical adsorption, biological oxidation and flocculation processes are generally used. However, these processes have their own defects to a greater or lesser extent, such as poor decomposition performance of organic pollutants, high process cost, low selectivity and easy to cause secondary pollution. As an advanced oxidation process, photocatalytic technology can effectively convert solar energy into chemical energy, and the implementation environment is relatively simple and convenient, with low cost and high efficiency, so it has become a research hotspot in the field of energy at this stage. In order to avoid secondary pollution and make the catalyst easy to recycle and reuse, the present invention prepares a magnetically recyclable photocatalyst. Summary of the invention
[0003] In order to improve the photocatalytic performance and recycling rate and avoid secondary pollution, the present invention provides a preparation method and application of CoFe2O4@BaTiO3 nano core-shell particles. The CoFe2O4@BaTiO3 nano core-shell particles are a magnetically recoverable photocatalyst.
[0004] Technical solution: A method for preparing CoFe2O4@BaTiO3 nano core-shell particles, comprising the following steps:
[0005] Step 1, preparing CFO by hydrothermal method;
[0006] Step 1.1, adding Fe(NO3)3·6H2O and Co(NO3)3·6H2O into deionized water and stirring to obtain solution P1; adding NaOH into deionized water and stirring to obtain solution P2;
[0007] Step 1.2, place P2 in a water bath, slowly pour P1 into P2, stir for a while, and then put it into a stirring hydrothermal reactor for reaction;
[0008] Step 1.3, after the reaction is completed, the precipitate is washed with deionized water and dried to obtain a CoFe2O4 powder sample, which is recorded as CFO;
[0009] Step 2, preparing CoFe2O4@BaTiO3 nano core-shell particles;
[0010] Step 2.1: Add CFO powder sample, CTAB and deionized water into a solution containing C4H 10O in a beaker to obtain suspension solution A;
[0011] Step 2.2, drop Ti(OC4H9)4 into the mixture containing C4H 10 O in a beaker and stirred evenly to obtain solution B;
[0012] Step 2.3, adding solution B dropwise to the suspension solution A, continuing to use mechanical stirring for a period of time after the addition is completed, collecting the precipitate, and then washing and drying with anhydrous ethanol to obtain CoFe2O4@TiO2 powder, and then grinding it into powder after drying to obtain CoFe2O4@TiO2 powder;
[0013] Step 2.4, dissolve Ba(OH)2·8H2O in deionized water, add CoFe2O4@TiO2 powder and perform ultrasound, then transfer the liquid to the PPM liner, put it in an oven and stir to react for a period of time, collect the solid product, wash it until the pH value is neutral, and dry it to obtain CoFe2O4@BaTiO3 nano core-shell particles.
[0014] Furthermore, in step 2:
[0015] The molar ratio of CFO to Ti(OC4H9)4 is 1:(6-30); the molar ratio of Ti(OC4H9)4 to Ba(OH)2·8H2O is 1:13.
[0016] Furthermore, in the step 1.1, the mass ratio of Fe(NO3)3·6H2O, Co(NO3)3·6H2O, and NaOH is 13.7359:4.9476:6.528;
[0017] The step 1.2 is specifically as follows: P2 is placed in a water bath at 30°C, P1 is slowly poured into P2 within 30s under mechanical stirring, stirred for 10min, and then placed in a stirring hydrothermal reactor, and reacted at a temperature of 200°C for 4h;
[0018] Step 1.3: Drying conditions: 60°C temperature, drying for 12 hours.
[0019] Further, the step 2.1 is specifically as follows: 0.001 mol of CFO powder sample, 0.5 g of CTAB and 10 mL of deionized water are added together with 200 mL of C4H 10 O in a beaker, sonicate for 20 min to disperse CFO and dissolve CTAB, and use an ultrasonic cell disruptor for 30 min to obtain a suspension solution A;
[0020] The specific step 2.2 is as follows: using a pipette, drop 0.006 mol-0.03 mol of Ti(OC4H9)4 into a 50 mL C4H10 O in a beaker and stirred magnetically for 30 min to obtain solution B;
[0021] The step 2.3 is specifically as follows: using a peristaltic pump to drop solution B into the suspension solution A within 30 minutes, during which mechanical stirring and ultrasonic treatment are used, and after the dropwise addition is completed, mechanical stirring is continued for 12 hours, and then the precipitate is collected; after the precipitate is washed with anhydrous ethanol, it is dried at 60° C. for 2 hours to obtain CoFe2O4@TiO2 powder, and after drying, it is ground into powder to obtain CoFe2O4@TiO2 powder;
[0022] Step 2.4, dissolve 0.0078-0.039 mol of Ba(OH)2·8H2O in 120 mL of deionized water, and stir in a water bath at 60°C until completely dissolved; add the CFO@BTO powder prepared in step 2.3 and ultrasonicate for 10 minutes, transfer the liquid to the PPM liner, put it in an oven and stir at 200°C for 4 hours; collect the solid product, wash it once with CH3COOH solution, and then wash it several times with deionized water until the pH value is neutral, and dry the product in an oven at 60°C to finally obtain CoFe2O4@BaTiO3 nano core-shell particles.
[0023] The CoFe2O4@BaTiO3 nano core-shell particles can be used to catalyze the decomposition of organic pollutants under any of the following conditions: visible light, ultrasonic field, visible light and ultrasonic field synergy, and visible light and magnetic field synergy. The magnetic field intensity range is 15mT-50mT; the visible light wavelength is: xenon lamp, 190nm-1100nm; the ultrasonic frequency range of the ultrasonic field is: 20-40kHz. The organic pollutant is rhodamine B.
[0024] Beneficial effects:
[0025] The core-shell samples prepared by the present invention have no other impurities and have uniform particle size distribution; compared with single-phase materials, the photocatalytic performance of the core-shell samples is significantly improved; the core-shell samples can be magnetically recovered to improve the recycling efficiency of the catalyst and reduce secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD pattern of the CFO sample prepared in Example 1.
[0027] Figure 2 This is a morphology photograph of CoFe2O4 nanoparticles observed using a transmission electron microscope.
[0028] Figure 3 is the XRD pattern of x-CFO@BTO prepared in Implementation 1.
[0029] Figure 4This is a morphology photograph of x-CFO@BTO (x=0.07) observed using a transmission electron microscope.
[0030] Figure 5 VSM diagrams of CFO and x-CFO@BTO (x=0.03, 0.07 and 0.15) samples.
[0031] Figure 6 Schematic diagram of the catalytic performance of x-CFO@BTO (x=0.03, 0.07 and 0.15) core-shell samples towards pollutants.
[0032] Figure 7 The figure shows the cyclic experimental process of photocatalytic degradation of RhB by x-CFO@BTO (x=0.07). DETAILED DESCRIPTION
[0033] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0034] Example 1
[0035] This embodiment provides a method for preparing nano core-shell particles CFO@BTO that can be magnetically recovered, has high mass production, and is free of impurities. This embodiment controls the generation of the compound CFO@BTO with a suitable temperature and a reasonable reaction time.
[0036] In this embodiment, a series of CoFe2O4@BaTiO3 (abbreviated as CFO@BTO) core-shell composite samples were prepared, in which the molar percentages of CFO were 3%, 7% and 15%, respectively. The samples were marked as x-CFO@BTO (x=0.03, 0.07 and 0.15), respectively. At the same time, the preparation methods of 7% CFO@BTO (Mixture) and pure phase BTO were provided.
[0037] (i) x-CFO@BTO (x=0.07) sample, the specific preparation method includes the following steps:
[0038] Step 1: Preparation of CFO:
[0039] Step 1.1, weigh 13.7359 g of Fe(NO3)3·6H2O and 4.9476 g of Co(NO3)3·6H2O into a 150 mL beaker, add 68 mL of deionized water and stir to obtain solution P1, weigh 6.528 g of NaOH into a 250 mL beaker, add 32.6 mL of deionized water and stir to obtain solution P2;
[0040] Step 1.2, place P2 in a water bath at 30°C, slowly pour P1 into P2 within 30 seconds under mechanical stirring, stir for 10 minutes at a speed of 500 rpm / min, then put into a stirring hydrothermal reactor, react at a temperature of 200°C for 4 hours at a speed of 100 rpm / min;
[0041] Step 1.3: After the reaction is completed, the precipitate is washed three times with deionized water, and then placed in an oven and dried at 60°C for 12 hours to obtain a final product, namely a CoFe2O4 powder sample, marked as CFO.
[0042] Step 2: Preparation of x-CFO@BTO (x=0.07):
[0043] Step 2.1, weigh 0.235g CFO (0.001mol) powder sample, 0.5g C 19 H 42 BrN(CTAB) and 10 mL of deionized water were added to a solution containing 200 mL of C4H 10 O in a beaker (beaker capacity is 500 mL), ultrasonicate for 20 min to disperse CFO and dissolve CTAB to obtain a suspension solution; use an ultrasonic cell disruptor to treat the suspension solution for 30 min to form a more uniform suspension solution A;
[0044] Step 2.2: Use a pipette to drop 4.44 mL (0.013 mol) of Ti(OC4H9)4 into a 50 mL solution of C4H 10 O in a beaker (beaker capacity: 100 mL) and magnetically stirred for 30 min (500 rpm) to obtain solution B;
[0045] Step 2.3, using a peristaltic pump to slowly drop solution B into the suspension solution A within 30 minutes, during which mechanical stirring (350 rpm) and ultrasound (300 W) were used. After the dropwise addition was completed, mechanical stirring was continued for 12 hours (350 rpm), and then the solution was collected;
[0046] The sample was washed with anhydrous ethanol for more than three times, dried at 60°C for 2h to obtain CoFe2O4@TiO2 powder, and then ground into powder using a mortar after drying;
[0047] Step 2.4: Dissolve 5.33 g (0.0169 mol) of Ba(OH)2·8H2O in 120 mL of deionized water and stir in a 60°C water bath until completely dissolved. Add CoFe2O4@TiO2 powder and sonicate for 10 min. Transfer the liquid to a 200 mL PPM liner and place in an oven and stir at 200°C for 4 h (300 rpm).
[0048] The solid product was collected, washed once with 3 mol / L CH3COOH solution to remove BaCO3 impurities in the sample, washed several times with deionized water until the pH value was neutral, and dried in an oven at 60°C to finally obtain the CFO@BTO core-shell sample.
[0049] (ii) Preparation of x-CFO@BTO (x = 0.03) and x-CFO@BTO (x = 0.15) samples
[0050] When preparing x-CFO@BTO (x=0.03) and x-CFO@BTO (x=0.15) samples, the amount of CFO remains unchanged. Only the amount of tetrabutyl titanate Ti(OC4H9)4 and barium hydroxide Ba(OH)2·8H2O needs to be changed. The rest is the same as the preparation of x-CFO@BTO (x=0.07) sample.
[0051] 1) When preparing the x-CFO@BTO (x=0.03) sample, CFO is 0.235 g (0.001 mol), Ti(OC4H9)4 is 10 mL (0.03 mol), and Ba(OH)2·8H2O is 12.3 g (0.039 mol).
[0052] 2) When preparing the x-CFO@BTO (x=0.15) sample, CFO was 0.235 g (0.001 mol), Ti(OC4H9)4 was 2.042 mL (0.006 mol), and Ba(OH)2·8H2O was 2.46 g (0.0078 mol).
[0053] (III) 7% CFO@BTO (Mixture) refers to a mixture of pure CFO and pure BTO, and the molar percentage of CFO in the mixture is 7%.
[0054] (IV) Preparation method of pure phase BTO
[0055] BaTiO3 (BTO) powder samples were prepared by traditional hydrothermal method. The specific experimental steps are as follows:
[0056] (1) Add 1.0 mL of Ti(OC4H9)4 to 50 mL of C4H 10 O, and magnetically stir for 30 min to obtain a clear solution, add 10 mL of deionized water, and magnetically stir for 12 h. The suspension is washed three times with ethanol and placed in a 60 ° C oven for drying to obtain a precursor product, which is then ground into powder.
[0057] (2) Weigh 1.203 g of Ba(OH)2·8H2O and place it in 133 mL of deionized water. Stir at 60°C for 20 min. Add the precursor powder and ultrasonicate for 20 min (300 W) to make it evenly dispersed. Transfer the solution to a 200 mL reactor and hydrothermally heat at 200°C for 4 h to collect the solid product S1.
[0058] (3) Pour 44 mL of CH3COOH into a 250 mL quantitative bottle, then pour deionized water to the neck mark. Invert the quantitative bottle repeatedly and shake it several times to obtain a 3 mol / L CH3COOH solution.
[0059] (4) The solid product S1 was washed once with a 3 mol / L CH3COOH solution to remove the BaCO3 impurities in the sample, and then washed several times with deionized water until the supernatant showed neutrality after a pH test paper test. The precipitate was obtained after centrifugation and dried for 12 h to obtain the final product, which was a BaTiO3 nanopowder sample, labeled as BTO.
[0060] (V) Product characterization:
[0061] Figure 1 The XRD pattern of the CFO sample prepared in 1 is as follows: Figure 1 It can be seen that the diffraction peaks appearing at 30.15°, 35.65°, 43.35°, 53.85°, 57.35°, and 62.80° correspond to the (220), (311), (400), (422), (511), and (440) crystal planes of spinel CoFe2O4, respectively. The selected standard card is PDF#22-1086.
[0062] Figure 2 The morphology of CoFe2O4 nanoparticles (CFO) observed by transmission electron microscopy, where (a) and (b) are TEM images of CoFe2O4; (c)-(h) are mapping element mapping images; (g) is the EDX spectrum. Figure 2 As can be seen from (a) and (b), the particle size distribution of the CoFe2O4 sample prepared by the hydrothermal method is uniform, and single particle dispersion can be achieved. By counting 100 particles, the average particle size is about 15nm. The small-sized particles lay a good foundation for the subsequent BaTiO3 shell coating. (c)-(h) are the mapping element results of CoFe2O4. The Co, Fe, and O elements are evenly distributed and there are no other elements. (i) is the EDX of CFO, indicating that there are only Co, Fe, and O elements in the sample, indicating that the present invention has prepared pure phase impurity-free CoFe2O4 nanoparticles with good crystallization.
[0063] Figure 3These are the XRD patterns of x-CFO@BTO (x=0.03, 0.07 and 0.15), where (a) is the XRD pattern of core-shell samples with different CFO molar ratios, and (b) is the crystal plane corresponding to x-CFO@BTO (x=0.07). Figure 3 It can be seen that the characteristic peak of CFO is relatively low, which is due to the low content of CFO in the core-shell structure sample. As the CFO content increases, the peak intensity of its characteristic peak gradually increases. The XRD diffraction peaks of all samples correspond to the standard spectra of CFO and BTO, and no other impurity peaks appear, indicating that the samples have a high degree of crystallinity.
[0064] Figure 4 The morphology of x-CFO@BTO (x=0.07) observed by transmission electron microscopy; Figure 4 Figures (a) and (b) are TEM images of x-CFO@BTO (x=0.07) nanoparticles observed by transmission electron microscopy. Different contrasts were observed in the particle morphology, revealing the formation of a core-shell structure. The dark area is the CFO phase, the gray area is the BTO phase, and the CFO nanoparticles are encapsulated in BTO to form a core-shell structure. Figure 4 (c)-(h) are the semi-quantitative analysis results of the mapping elements of x-CFO@BTO (x=0.07). The Ba, Ti, Co, Fe, and O elements are evenly distributed without other elements. The Ba and Ti elements are wrapped around the Co and Fe elements, which indicates that the CFO nanoparticles prepared by the present invention are wrapped by BTO. Figure 4 (i) is the EDX spectrum of x-CFO@BTO (x=0.07), indicating that the CFO@BTO core-shell structure sample prepared by the present invention is free of impurities and has good crystallization.
[0065] Figure 5 VSM diagrams of CFO and x-CFO@BTO (x = 0.03, 0.07 and 0.15) samples, Figure 5 The hysteresis loops of CFO and x-CFO@BTO (x=0.03, 0.07 and 0.15) samples at room temperature are shown. As can be seen from the figure, the Ms value of the single-phase CFO sample reaches 65.6emu / g. With the increase of CFO content, the magnetism of the core-shell sample increases, and the saturation magnetization Ms of the x-CFO@BTO (x=0.03, 0.07 and 0.15) samples increases (6.23, 11.9 and 30.375emu / g, respectively). The magnetism of the composite sample comes from the CFO core layer.
[0066] (vi) To evaluate the catalytic performance of x-CFO@BTO (x=0.03, 0.07 and 0.15) core-shell samples on pollutants, this example uses rhodamine B (RhB) dye as the target pollutant, and performs degradation experiments on RhB under four conditions: visible light (photocatalysis), ultrasonic field (acoustic catalysis), ultrasonic field synergistic with visible light (acoustic-photosynergistic catalysis), and different magnetic field intensities synergistic with visible light (magneto-photosynergistic catalysis). When conducting the catalytic performance test, the concentration of rhodamine B in the target pollutant is 5 mg / L, the volume of the target pollutant is 50 mL, the amount of the catalyst is 50 mg, the wavelength of the visible light is 400 nm-700 nm, and the vibration frequency / power of the ultrasonic field is 40 kHz / 300 W.
[0067] The results are as follows Figure 6 shown. Figure 6 The catalytic performance of pure BTO, core-shell samples with different proportions, and a pure mixture with a CFO ratio of 7% under (a) visible light only, (b) ultrasonic field only, and (c) sound-light synergistic conditions, (d)-(f) are the corresponding ln(C0 / C)-t relationship diagrams; (g) is the catalytic performance under the synergistic conditions of magnetic field and visible light, and (h) is the corresponding ln(C0 / C)-t relationship diagram; (i) is the catalytic performance of x-CFO@BTO (x=0.07) under visible light and different magnetic field intensities, and (j) is the corresponding ln(C0 / C)-t relationship diagram.
[0068] Figure 6 (a) shows that after 100 minutes of visible light irradiation, the single-phase BTO degraded about 68% of the RhB dye. In contrast, the catalytic performance of the core-shell structure of CFO@BTO is improved, and with the increase of CFO content, its catalytic performance first increases and then decreases. The x-CFO@BTO (x = 0.03) sample has the best photocatalytic performance, with a degradation rate of 78% for RhB within 100 minutes. According to the Lambert-Beer theory, the corresponding ln(C0 / C)-t curve is as follows Figure 6 As shown in (d), the catalytic reaction rate of x-CFO@BTO (x = 0.03) is the fastest, reaching 0.01544 min -1 , which is 1.15 times that of single-phase BTO. Compared with single-phase BTO, the photocatalytic performance of the core-shell sample of CFO@BTO is significantly improved. This may be because CFO broadens the light response absorption range and improves the sample's absorption capacity of visible light, thereby improving the photocatalytic performance. However, as the CFO content continues to increase to 0.07, the sample's magnetism increases, causing the nanopowder sample to easily agglomerate and the performance to decline.
[0069] Figure 6(b) shows that after 60 minutes of sonocatalysis, the single-phase BTO degraded about 97% of the RhB dye. With the increase of CFO content, the sonocatalytic performance first increased and then decreased. Among them, the sonocatalytic performance of x-CFO@BTO (x = 0.07) was the best, and the RhB degradation rate reached 100% within 50 minutes. According to the Lambert-Beer theory, the ln (C0 / C)-t curve corresponding to the sample sonocatalysis is shown in Figure 6 As shown in (e), the catalytic reaction rate of x-CFO@BTO (x = 0.07) is the fastest, reaching 0.13989 min -1 , which is about 1.95 times that of single-phase BTO. The above results show that the sonocatalytic performance of the sample after BTO and CFO are composited is significantly improved.
[0070] Figure 6 (c) shows that after 60 minutes of simultaneous irradiation with visible light and ultrasound, the degradation rate of RhB by single-phase BTO reached 99.8%. The sono-photocatalytic performance of the sample after BTO and CFO composite was further improved. The sono-photocatalytic efficiency of the x-CFO@BTO (x = 0.07) sample reached the best, and the degradation rate of RhB solution reached 100% within 40 minutes. According to the Lambert-Beer theory, the ln(C0 / C)-t curve corresponding to the sono-catalytic performance of the sample is as follows: Figure 6 As shown in (f), the rate of the sono-photocatalytic synergistic reaction of x-CFO@BTO (x = 0.07) reaches 0.15837 min -1 , which is about 1.62 times that of single-phase BTO.
[0071] It is worth mentioning that the reaction rate constant (0.15837min) of the x-CFO@BTO (x = 0.07) sample under simultaneous irradiation of visible light and ultrasound is -1 ) is greater than visible light (0.1132min -1 ), ultrasound (0.13989min -1 ) alone, showing a positive synergistic effect. The results show that the CFO@BTO core-shell sample improves the sono-photocatalytic activity.
[0072] Figure 6 (g) shows the performance of each sample in the degradation of RhB under the combined action of magnetic field (15mT) and visible light (magneto-optical synergy). The performance of BTO did not improve significantly, while the performance of CFO@BTO samples improved significantly, among which x-CFO@BTO (x=0.07) had the best performance, which was about 1.4 times higher than that of single-phase BTO after 120 minutes of magneto-optical synergy. The ln(C0 / C)-t curve corresponding to the sample sonocatalysis is shown in Figure 2. Figure 6 As shown in (h), it can be seen that the magnetic field has a significant promoting effect on the photocatalytic reaction of the CFO@BTO sample.
[0073] Depend on Figure 6 As can be seen in (i), with the increase of magnetic field intensity, the photocatalytic performance of CFO@BTO samples first increases and then decreases. When the external magnetic field intensity is 25mT, the photocatalytic performance of x-CFO@BTO (x = 0.07) is the best, and after 120 minutes of magneto-optical synergy, it is improved by about 1.6 times compared with single-phase BTO. The ln(C0 / C)-t curve corresponding to the sample acoustic catalysis is shown in Figure 6 As shown in (j), the magnetic field promotes the improvement of photocatalytic reaction, and its mechanism can be explained as follows: when an external magnetic field acts on the sample, the magnetoelectric effect of the magnetoelectric core-shell sample (CFO@BTO sample) enhances the electric polarization field of BTO. The enhancement of this polarization field provides a greater driving force for the separation of photogenerated carriers, greatly improving the separation rate of carriers, thereby improving the photocatalytic performance.
[0074] Figure 7 (a) is a schematic diagram of the cyclic experimental process of x-CFO@BTO (x=0.07) sono-photocatalytic degradation of RhB; (b) is the XRD diagram of x-CFO@BTO (x=0.7) before and after the cyclic experiment; (c) is the picture before recycling; and (d) is the comparison picture after recycling. Figure 7 (a) is a cycle experiment of x-CFO@BTO (x = 0.07) sample to degrade RhB. After 5 consecutive magnetic recovery cycle experiments, the degradation efficiency loss of the sono-photocatalytic performance was less than 5%. At the same time, the XRD of the catalyst sample before and after the 5 cycle experiments was compared, and it was found that the XRD diffraction peaks of the sample remained basically unchanged, such as Figure 7 As shown in (b), the above two aspects indicate that the x-CFO@BTO (x=0.07) sample has excellent chemical stability and recyclability. Figure 7 (c) and gives the photos of the x-CFO@BTO (x=0.07) sample recovery using magnets in the experiment, and the BTO sample is used for comparison. The pictures after recovery are as follows Figure 7 As shown in (d). It can be seen that the CFO@BTO core-shell (electromagnetic core-shell particles) prepared by the present invention completed the movement and aggregation in the direction of the magnet within 1 minute under the action of the magnet, and the suspension became clear and transparent, while BTO did not have this phenomenon due to its lack of magnetism. The above experiments show that the magnetoelectric core-shell composite sample (CFO@BTO sample) can be magnetically recovered and recycled.
[0075] The present invention uses CoFe2O4 as the core and BaTiO3 as the shell to produce a CoFe2O4@BaTiO3 nanocore-shell particle. Although the magnetic field can affect the movement of electrons in the magnetic material, they cannot generate the internal electric field and charge required for the catalytic reaction. On the contrary, when the magnetic field is applied, the multiferroic magnetoelectric composite material (CoFe2O4@BaTiO3) will produce a magnetoelectric coupling effect. In this strain-mediated magnetoelectric composite material, the magnetic part of the catalyst will respond to the magnetic field and transfer the magnetostrictive strain to the ferroelectric / piezoelectric material through the interface interaction. The resulting electric polarization change will generate surface charge, which will then trigger the final catalytic reaction.
[0076] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.
Claims
1. A method for preparing CoFe2O4@BaTiO3 nano core-shell particles, characterized in that: The steps include: Step 1, preparing CFO by hydrothermal method; Step 1.1, adding Fe(NO3)3·6H2O and Co(NO3)3·6H2O into deionized water and stirring to obtain solution P1; adding NaOH into deionized water and stirring to obtain solution P2; Step 1.2, place P2 in a water bath, slowly pour P1 into P2, stir for a while, and then put it into a stirring hydrothermal reactor for reaction; Step 1.3, after the reaction is completed, the precipitate is washed with deionized water and dried to obtain a CoFe2O4 powder sample, which is recorded as CFO; Step 2, preparing CoFe2O4@BaTiO3 nano core-shell particles; Step 2.1: Add CFO powder sample, CTAB and deionized water into a solution containing C4H 10 O in a beaker to obtain suspension solution A; Step 2.2, drop Ti(OC4H9)4 into the mixture containing C4H 10 O in a beaker and stirred evenly to obtain solution B; Step 2.3, adding solution B dropwise to the suspension solution A, continuing to use mechanical stirring for a period of time after the addition is completed, collecting the precipitate, and then washing and drying with anhydrous ethanol to obtain CoFe2O4@TiO2 powder, which is then ground into powder after drying; Step 2.4, dissolve Ba(OH)2·8H2O in deionized water, add CoFe2O4@TiO2 powder and perform ultrasound, then transfer the liquid to the PPM liner, put it in an oven and stir to react for a period of time, collect the solid product, wash and dry it to obtain CoFe2O4@BaTiO3 nano core-shell particles.
2. The preparation method according to claim 1, characterized in that: In step 2: The molar ratio of CFO to Ti(OC4H9)4 is 1:(6-30); the molar ratio of Ti(OC4H9)4 to Ba(OH)2·8H2O is 1:
13.
3. The preparation method according to claim 1, characterized in that: In step 1.1, the mass ratio of Fe(NO3)3·6H2O, Co(NO3)3·6H2O, and NaOH is 13.7359:4.9476:6.528; The step 1.2 is specifically as follows: P2 is placed in a water bath at 30°C, P1 is slowly poured into P2 within 30s under mechanical stirring, stirred for 10min, and then placed in a stirring hydrothermal reactor, and reacted at a temperature of 200°C for 4h; Step 1.3: Drying conditions: 60°C temperature, drying for 12 hours.
4. The preparation method according to claim 1, characterized in that: The specific step 2.1 is as follows: 0.001 mol of CFO powder sample, 0.5 g of CTAB and 10 mL of deionized water are added together with 200 mL of C4H 10 O in a beaker, sonicate for 20 min to disperse CFO and dissolve CTAB, and use an ultrasonic cell disruptor for 30 min to obtain a suspension solution A; The specific step 2.2 is as follows: using a pipette, drop 0.006 mol-0.03 mol of Ti(OC4H9)4 into 50 mL of C4H 10 O in a beaker and stirred magnetically for 30 min to obtain solution B; The step 2.3 is specifically as follows: using a peristaltic pump to drop solution B into the suspension solution A within 30 minutes, during which mechanical stirring and ultrasonic treatment are used, and after the dropwise addition is completed, mechanical stirring is continued for 12 hours, and then the precipitate is collected; after the precipitate is washed with anhydrous ethanol, it is dried at 60° C. for 2 hours to obtain CoFe2O4@TiO2 powder, and after drying, it is ground into powder to obtain CoFe2O4@TiO2 powder; Step 2.4, dissolve 0.0078-0.039 mol of Ba(OH)2·8H2O in 120 mL of deionized water, and stir in a water bath at 60°C until completely dissolved; add the CoFe2O4@TiO2 powder prepared in step 2.3 and ultrasonicate for 10 minutes, transfer the liquid to the PPM liner, put it in an oven and stir at 200°C for 4 hours; collect the solid product, wash it once with CH3COOH solution, and then wash it several times with deionized water until the pH value is neutral, and dry the product in an oven at 60°C to finally obtain CoFe2O4@BaTiO3 nano core-shell particles.
5. The use of the CoFe2O4@BaTiO3 nano core-shell particles according to any one of claims 1 to 4, characterized in that: Used to catalyze the decomposition of organic pollutants under any conditions of visible light, ultrasonic field, visible light and ultrasonic field synergy, and visible light and magnetic field synergy.
6. Use according to claim 5, characterized in that The magnetic field intensity ranges from 15mT to 50mT; the visible light wavelength is: xenon lamp, 190nm-1100nm; the ultrasonic frequency range of the ultrasonic field is: 20-40kHz.
7. The use according to claim 5, characterized in that The organic pollutant is rhodamine B.